what do we get after expanding (p+3q-2z)^2?
Answers
Answered by
1
Answer:
What do we get after expanding (p+3q-2z)2? (p+3q-2z)2can also be written as (p+3q+(-2z))2. = p2 + 9q2 + 4z2 + 6pq – 12qz – 4zp.
Answered by
2
Answer:
Explanation: We know that (a+b+c)^2 = a^2 + b^2 + c^2 + 2ab + 2bc + 2ca
(p+3q-2z)^2can also be written as (p+3q+(-2z))^2.
Here, a = p, b = 3q and c = -2z
Therefore, using that formula we get (p+3q+(-2z))^2
= p^2 + (3q)^2 + (-2z)^2 + 2(p)(3q) + 2(3q)(-2z) + 2(-2z)(p)
= p^2 + 9q^2 + 4z^2 + 6pq – 12qz – 4zp.
Hope it was helpful!!
Similar questions